Endoplasmic reticulum-associated degradation mitigates atherosclerosis by maintaining cellular homeostasis - Niu, Haiming; Wu, Lin; Cai, Yingzhang; Yu, Conghui; Lin, Ning; Cai, Xiaodong; Chen, Miaolian; Wang, Linli (Frontiers in Physiology, 2025)
Atherosclerosis (AS) is a fatal cardiovascular disease (CVD) that threatens human health. Although there are some treatments for AS in clinical practice, cardiovascular complications such as myocardial ischemia and hypoxia, heart failure, and stroke often occur in different AS subgroups. Therefore, it is critical and necessary to screen and identify novel protein molecules to mitigate this disease. Unstable plaques of AS is the main cause for fatal consequences, so it is particularly urgent to find a treatment to stabilize plaques to prevent cardiovascular and cerebrovascular diseases. During the formation of plaque, a large amount of protein is produced and misfolded; this process initiates endoplasmic reticulum stress (ERS). Despite unfolded protein response (UPR) in the clearing of unfolded proteins, endoplasmic reticulum (ER)-associated degradation (ERAD) maintains ER proteostasis in mammalian cells by degrading misfolded proteins. However, the role of ERAD has not been fully elucidated in AS. In this review, the role of ERS in the different cells that took part in AS was summarized; then, the rescue function of ERAD in all the cell types was elucidated, especially vascular smooth muscle cells. An updated summary of the recent studies and systematic knowledge of ERAD in the mechanism of AS was presented, which may help guide future research and provide novel insights into the prevention and treatment of related diseases.